PENDIDIKAN ISLAM DI TENGAH PANDEMI COVID-19: UPAYA MEMBANGUN EMPATI WARGA SEKOLAH - Muhammad Abrar Parinduri; Umi Kultsum (Ta'dib, 2020)
Abstract: Empathy is the ability to understand the problems and feelings of others, to think from other people's points of view, and to be able to appreciate the differences in the feelings of others in response to various problems. The focus of this research lies in how the efforts to instill the values of empathy carried out by the Private Madrasah Aliyah Muhammadiyah-12 Punggulan of Asahan Regency in the midst of the Covid-19 pandemic. This research uses qualitative methods with field studies and literature studies. The results showed that the inculcation of the value of empathy in students was carried out in a motivational and planned way. The efforts made to instill the values of empathy include: First, the cultivation of the value of compassion for the meaning of life; Second, Friday blessings and the spirit of sharing; Third, be wise in using social media; Fourth, economic mapping of students' families as a form of madrasah empathy. The steps taken to make it happen are: First, the role model of the madrasa principal and teachers; Second, always provide motivation to students; Third, supervise students in using social media; Fourth, encourage students to carry out useful activities while studying at home, especially through the midnight prayer program at home only.Abstrak: Empati merupakan suatu kemampuan dalam memahami masalah dan perasaan orang lain, berpikir dengan menggunakan sudut pandang orang lain, serta mampu menghargai perbedaan perasaan orang lain dalam menanggapi  berbagai masalah. Fokus penelitian ini terletak pada bagaimana upaya penanaman nilai-nilai empati yang dilakukan Madrasah Aliyah Swasta Muhammadiyah-12 Punggulan Kabupaten Asahan di tengah kondisi pandemic covid-19. Penelitian ini menggunakan metode kualitatif dengan studi lapangan dan studi kepustakaan. Hasil penelitian menunjukkan bahwa penanaman nilai empati pada siswa dilakukan cara memotivasi dan juga terencana. Upaya yang dilakukan untuk menanamkan nilai-nilai empati tersebut antara lain: Pertama, penanaman nilai welas-asih untuk kebermaknaan hidup; Kedua, jum’at berkah dan semangat berbagi; Ketiga, bijak dalam penggunaan media sosial; Keempat, pemetaan ekonomi keluarga siswa sebagai wujud empati madrasah. Adapun langkah-langkah yang dilakukan untuk mewujudkannya adalah: Pertama, keteladanan dari kepala madrasah dan para guru; Kedua, senantiasa memberikan motivasi kepada siswa; Ketiga, melakukan pengawasan terhadap siswa dalam menggunakan media sosial; Keempat, mendorong siswa untuk melakukan aktifitas yang bermanfaat selama belajar di rumah khususnya melalui program sholat tahajjud di rumah saja.